Nutritionist Emergency Team sebagai Tim Tanggap Bencana di Universitas Respati Yogyakarta: Nutritionist Emergency Team as a Disaster Relief Team at Universitas Respati Yogyakarta - Widodo, Soepri Tjahjono Moedji; Inayah, Inayah; Metty, Metty (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Indonesia is one of the countries with a very high level of disaster vulnerability. In 2020, the National Disaster Management Agency recorded 1,792 disaster events that occurred in Indonesia from the beginning of January to July. Another task of students besides studying is as an agent of change or reform agent, where they are expected to bring positive changes for themselves, their families, and society. As agents of change, students can set an example for the community on how to act appropriately when facing a disaster. In this context, students need to have adequate knowledge about disaster preparedness. Objective: The formation of the Nutritionist Emergency Team as a team that is ready for disaster management at Respati University Yogyakarta. Methods: Disaster preparedness training that focuses on food service and production, namely making complementary foods and public kitchens for disaster survivors. The training is in collaboration with BPBD Sleman Regency and PMI Sleman Regency. The training was held for 3 months with activities held every Saturday and Sunday. The training participants were 15 students who were selected with certain criteria. Results: Increased knowledge and skills about student preparedness in disaster situations. Students can work to manage the MP_ASI kitchen and public kitchen. Conclusion: The Formation of Nutritionist Emergency Team at Respati University Yogyakarta.